1974
DOI: 10.1042/cs0460001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phenobarbitone on Plasma [14C]Bilirubin Clearance in Patients with Unconjugated Hyperbilirubinaemia

Abstract: 1. The clearance of a tracer dose of [14C]bilirubin from the plasma was studied in patients with Gilbert's syndrome, congenital non-haemolytic jaundice, haemolytic jaundice and in normal subjects. Clearance was significantly impaired in the patients with Gilbert's syndrome and in those with congenital non-haemolytic jaundice when compared with the normal subjects, and was normal in the patient with haemolytic jaundice. 2. Treatment for 2 weeks with phenobarbitone (180 mg/day) lowered the plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

1975
1975
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…Induction of bilirubin UGT is widely accepted as the mechanism by which phenobarbital therapy lowers serum bilirubin levels in individuals with unconjugated hyperbilirubinemia. 12,15,16,29 Fur- thermore, Sutherland et al 17 reported markedly higher UGT1A1 mRNA levels in 2 patients exposed to phenobarbital or the phenobarbital-like inducer, phenytoin, and in this study, the 3 donor samples with the highest levels of UGT1A1 protein were from individuals with a documented history of phenytoin therapy at the time of death. Yet our study revealed surprisingly weak hepatocyte UGT1A1-inducing effects of phenobarbital.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Induction of bilirubin UGT is widely accepted as the mechanism by which phenobarbital therapy lowers serum bilirubin levels in individuals with unconjugated hyperbilirubinemia. 12,15,16,29 Fur- thermore, Sutherland et al 17 reported markedly higher UGT1A1 mRNA levels in 2 patients exposed to phenobarbital or the phenobarbital-like inducer, phenytoin, and in this study, the 3 donor samples with the highest levels of UGT1A1 protein were from individuals with a documented history of phenytoin therapy at the time of death. Yet our study revealed surprisingly weak hepatocyte UGT1A1-inducing effects of phenobarbital.…”
Section: Discussionmentioning
confidence: 80%
“…14 Although bilirubin excretion is clearly increased in humans by phenobarbital, attempts to demonstrate that the effect is actually the result of elevated bilirubin UGT activity (i.e., UGT1A1) in human liver has had varied outcomes. 15,16 Following the identification of UGT1A1 as the major bilirubin glucuronidating UGT, 2,3 only 2 studies have specifically addressed the inducibility of hepatic UGT1A1 in primate species using UGT1A1-specific molecular probes. No effect of phenobarbital was observed on the UGT1A1 mRNA level in liver samples from phenobarbital-exposed monkeys.…”
mentioning
confidence: 99%
“…In addition, more complex models have been proposed to accommodate the bilirubin fractions derived from turnover ofhepatic heme and hemoproteins (12)(13)(14). These models have been used to interpret data derived from plasma radiobilirubin disappearance studies in various human disorders associated with unconjugated hyperbilirubinemia (13,(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14] Conjugated bilirubin is excreted into the bile. The bile is then passed to the duodenum via biliary system.…”
mentioning
confidence: 99%